2008
DOI: 10.1088/0031-9155/53/4/020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of Monte Carlo proton transport at grazing incidence in GEANT4, FLUKA and MCNPX

Abstract: The ability of the Monte Carlo (MC) particle transport codes GEANT4.8.1 and GEANT4.8.2, FLUKA2006 and MCNPX2.4.0 to model proton transport at grazing incidence onto tungsten blocks has been tested and compared to experimental measurements. The test geometry consisted of a narrow proton beam of two energies, 98 MeV and 180 MeV, impinging on a thick tungsten alloy block at grazing incidence. The distribution of forward out-scatter from the tungsten alloy block was measured with a fluorescent screen viewed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…MCNPX results had a wider FWHM than those for GEANT4, leading to a lower depth dose on the central axis. Similar findings were reported by Kimstrand et al [13] However, Kimstrand et al also compared experimental data with GEANT4, MCNPX, and FLUKA and concluded that all of these codes underestimated the probability of outscatter. MCS can be accurately modelled only if careful tuning of transport parameters was performed.…”
Section: Dose Contribution Of Different Kinds Of Particlessupporting
confidence: 79%
See 2 more Smart Citations
“…MCNPX results had a wider FWHM than those for GEANT4, leading to a lower depth dose on the central axis. Similar findings were reported by Kimstrand et al [13] However, Kimstrand et al also compared experimental data with GEANT4, MCNPX, and FLUKA and concluded that all of these codes underestimated the probability of outscatter. MCS can be accurately modelled only if careful tuning of transport parameters was performed.…”
Section: Dose Contribution Of Different Kinds Of Particlessupporting
confidence: 79%
“…The simulation of proton transport under these conditions has to be carefully studied in order to obtain accurate results. [13] Comparisons of MC simulations and the pencil beam algorithm may help to clarify dose distribution under proton disequilibrium, which is likely to occur in lung dosimetry. The subcentimetre lateral dose distribution was also studied to understand the dose deviation between different MC simulations and the pencil beam algorithm.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple groups have developed Monte Carlo treatment planning engines (Tourovsky et al , 2005; Newhauser et al , 2008b; Perl et al , 2012; Mairani et al , 2013) based on various Monte Carlo codes, independently proving the technical feasibility of this approach. The physics of general purpose Monte Carlo codes for this purpose has been exhaustively validated against benchmark measurements in therapeutic proton beam data (Polf JC, 2007; Kimstrand et al , 2008; Titt et al , 2008a; Randeniya et al , 2009). Just 10 years ago, the slow execution times, memory constraints, unknown accuracy, and unknown technical feasibility of a full-blown Monte Carlo engine were serious research challenges.…”
Section: Proton Transport Calculationsmentioning
confidence: 99%
“…All these general purpose codes with careful choice of approximations produce accurate results for proton transport compared to experiments. [22232425262728]…”
Section: Introductionmentioning
confidence: 99%